Barrels XXVIII take the Windy City by storm. (2nd January 2016) - Gour, Anjali; Lyall, Evan H.; Naka, Alexander; Brumberg, Joshua C.
Abstract: The 28th annual Barrels meeting was held prior to the Society for Neuroscience meeting in October 2015 at the Northwestern University School of Law in Chicago, Illinois. The meeting brought together researchers focused on the rodent sensorimotor system. The meeting focused on modern techniques to decipher cortical circuits, social interactions among rodents, and decision-making. The meeting allowed investigators to share their work via short talks, poster presentations, and a data blitz.